2020
DOI: 10.7554/elife.61298
|View full text |Cite
|
Sign up to set email alerts
|

A small number of workers with specific personality traits perform tool use in ants

Abstract: Ants use debris as tools to collect and transport liquid food to the nest. Previous studies showed that this behaviour is flexible whereby ants learn to use artificial material that is novel to them and select tools with optimal soaking properties. However, the process of tool use has not been studied at the individual level. We investigated whether workers specialise in tool use and whether there is a link between individual personality traits and tool use in the ant Aphaenogaster senilis. Only a small number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…Fast explorers in the open-field took more time to approach the ambiguous stimulus compared to slow explorers. Maák et al (2020) revealed a link between behavioral traits and tool use in A. senilis. This species has long been known as the user of debris to transport liquid food (Fellers and Fellers, 1976;reviews in Lőrinczi et al, 2018;Maák et al, 2020).…”
Section: Behavioral and Cognitive Individual Variability In Group Recruiting Antsmentioning
confidence: 96%
See 4 more Smart Citations
“…Fast explorers in the open-field took more time to approach the ambiguous stimulus compared to slow explorers. Maák et al (2020) revealed a link between behavioral traits and tool use in A. senilis. This species has long been known as the user of debris to transport liquid food (Fellers and Fellers, 1976;reviews in Lőrinczi et al, 2018;Maák et al, 2020).…”
Section: Behavioral and Cognitive Individual Variability In Group Recruiting Antsmentioning
confidence: 96%
“…Maák et al (2020) revealed a link between behavioral traits and tool use in A. senilis. This species has long been known as the user of debris to transport liquid food (Fellers and Fellers, 1976;reviews in Lőrinczi et al, 2018;Maák et al, 2020). Maák et al (2020) tested tool-using abilities in individuals using two tests, open-field and reaction to prey.…”
Section: Behavioral and Cognitive Individual Variability In Group Recruiting Antsmentioning
confidence: 96%
See 3 more Smart Citations